Penerapan Akad Syirkah pada PT. Barokah Biqalbin Salim Rumah Jahit Akhwat (RJA) Makassar dalam Perspektif Fikih Muamalah - Khaerul Aqbar; Awal Rifai; Erlangga Erlangga (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to know and understand the concept of syirkah in Islamic law and its application to PT. Barokah Biqalbin Salim Akhwat Sewing House (RJA) Makassar. This research is a field research which is a qualitative research using normative juridical approach and sociological approach. The results of the research show the following: first, the implementation of the syirkah contract applied to PT. Barokah Biqalbin Salim Akhwat Sewing House (RJA) Makassar is included in the syirkah al-Muḍārabah category where investors provide capital in the form of money with different nominal values to the manager, on the other hand the manager also has capital in the business. The implementation of the contract does not conflict with the meaning, intent and purpose of the syirkah contract nor does it conflict with the terms and pillars of syirkah. second, the jurists agree that the permissibility of syirkah al-Muḍārabah is based on consensus based on the verses of the Qur'an and hadith. Application of syirkah al-Muḍārabah at PT. Barokah Biqalbin Salim Akhwat Sewing House (RJA) Makassar is in accordance with the Shari'a which is strengthened by the fatwas of contemporary scholars. The mistakes that occur in the contract are that the manager often experiences delays in reporting sales results, but this is just a technical error and has no impact at all on business losses. For that PT. Barokah Biqalbin Salim Akhwat Sewing House (RJA) Makassar needs to continue to evaluate in order to achieve maximum cooperation so that there will be more jobs for Muslims in need.